Pengelolaan Pembelajaran Matematika Sekolah Standar Nasional - Sutama, Sutama; Suryo Putro, Kucisti Ike Retnaningtyas (Delta Jurnal Ilmiah Pendidikan Matematika FKIP Universitas Pekalongan, 2013)
The general objectives of this study are to describe mathematicslearning management at National Standard School of Junior HighSchool 1 Karangkobar Banjarnegara. Then, the specific objectives areto describe the characteristics of its (1) room and media, (2) materialand (3) mathematics learning interaction. This qualitative researchuses observation, in-depth interviews, and documentation forcollecting the data. Informants are from mathematics teachers,teachers who like and dislike mathematics, and the students. Data areanalyzed by using single site in the frame of flow method qualitativeanalysis. Method and source triangulation are used to measure the datavalidity.The results show (1) room management creates effective andproductive mathematics learning and media management increasesmotivation and concept understanding, (2) holistically learningmaterial management results optimal learning outcome and variationin learning material develops the reflective thinking of students, (3)interaction management makes the learning process lively and happilyand finally the goals are reached.Keywords: management, space, media, learning material, interaction